2022
DOI: 10.1186/s12961-022-00929-9
|View full text |Cite
|
Sign up to set email alerts
|

Degree of protection provided by poverty alleviation policies for the middle-aged and older in China: evaluation of effectiveness of medical insurance system tools and vulnerable target recognition

Abstract: Background China’s medical insurance schemes and poverty alleviation policy at this stage have achieved population-wide coverage and the system's universal function. At the late stage of the elimination of absolute poverty task, how to further exert the poverty alleviation function of the medical insurance schemes has become an important agenda for targeted poverty alleviation. To analyse the risk of catastrophic health expenditure (CHE) occurrence in middle-aged and older adults with vulnerabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This might have something to do with the fact that inpatient care has higher reimbursement rates and more medical services than outpatient care ( 38 ). Existing research has shown that health insurance has little association with the out-of-pocket cost of outpatient services, and patients can only receive greater reimbursement through inpatient care ( 36 , 39 , 40 ). This suggests that patients would reduce their use of outpatient care in favor of more inpatient care ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…This might have something to do with the fact that inpatient care has higher reimbursement rates and more medical services than outpatient care ( 38 ). Existing research has shown that health insurance has little association with the out-of-pocket cost of outpatient services, and patients can only receive greater reimbursement through inpatient care ( 36 , 39 , 40 ). This suggests that patients would reduce their use of outpatient care in favor of more inpatient care ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the government should strengthen the management and regulation of medical institutions, enhance the supervision of the quality of medical services, and ensure the medical safety and rights of the elderly. Finally, the government should strengthen the publicity and education of the healthcare system for the elderly, improve the elderly's understanding of and awareness of healthcare, and enhance their awareness of healthcare protection [2].…”
Section: The Concept and Current Status Of Medical Coverage For The E...mentioning
confidence: 99%
“…This definition aligns with previous research [ 9 14 ]. In China, due to ‘China’s One Child Policy‘ adopted in 1979 [ 15 ] and the lack of a social nursing insurance system [ 16 ] and nursing homes [ 17 ], caregivers experience a much heavier burden than before. It has also been reported that older adults living in the community have a higher percentage of unmet ADL needs—approximately 56% in a population-representative study conducted in China [ 18 ].…”
Section: Introductionmentioning
confidence: 99%